Pengaruh Brand Image Dan Kualitas Produk Terhadap Kepuasan Pelanggan Generasi Z Pada Produk Zara Mall Kota Kasablanka Jakarta Selatan - Fadillah Khairunnisa J; Harimurti Wuladjani (JURNAL MANAJEMEN PENDIDIKAN, 2026)
The Influence of Brand Image and Product Quality on Generation Z Customer Satisfaction in Zara Mall Kota Kasablanka South Jakarta Products This study aims to analyze the influence of Brand Image and Product Quality on Customer Satisfaction among Generation Z consumers of Zara products at Kota Kasablanka Mall, South Jakarta. The study is motivated by the increasingly competitive fast fashion industry, requiring companies to establish a strong brand image and provide high-quality products to enhance customer satisfaction. Generation Z was selected as the research subject because this generation actively follows fashion trends and exhibits unique consumer behavior characteristics. This research employed a quantitative method with descriptive and causal associative approaches. Data were collected through questionnaires distributed to Generation Z consumers who had purchased and used Zara products at Kota Kasablanka Mall, South Jakarta. The data were analyzed using multiple linear regression analysis.The findings reveal that Brand Image has a positive and significant effect on Customer Satisfaction. Product Quality also has a positive and significant effect on Customer Satisfaction. Furthermore, Brand Image and Product Quality simultaneously have a positive and significant effect on Customer Satisfaction. These findings indicate that a strong brand image and product quality that meet consumer expectations are important factors in enhancing the satisfaction of Generation Z customers toward Zara products.